The Ignorant Citizen: Mouffe, Rancière, and the Subject of Democratic Education - Biesta, Gert (Studies in philosophy and education, 2011)
Much work in the field of education for democratic citizenship is based on the idea that it is possible to know what a good citizen is, so that the task of citizenship education becomes that of the production of the good citizen. In this paper I ask whether and to what extent we can and should understand democratic citizenship as a positive identity. I approach this question by means of an exploration of four dimensions of democratic politics—the political community, the borders of the political order, the dynamics of democratic processes and practices, and the status of the democratic subject—in order to explore whether and to what extent the ‘essence’ of democratic politics can and should be understood as a particular order. For this I engage with ideas from Chantal Mouffe and Jacques Rancière who both have raised fundamental questions about the extent to which the ‘essence’ of democratic politics can be captured as a particular order. In the paper I introduce the figure of the ignorant citizen in order to hint at a conception of citizenship that is not based on particular knowledge about what the good citizen is. I introduce a distinction between a socialisation conception of citizenship education and civic learning and a subjectification conception of citizenship education and civic learning in order to articulate what the educational implications of such an ‘anarchic’ understanding of democratic politics are. While the socialisation conception focuses on the question how ‘newcomers’ can be inserted into an existing political order, the subjectification conception focuses on the question how democratic subjectivity is engendered through engagement in always undetermined political processes. This is no longer a process driven by knowledge about what the citizen is or should become but one that depends on a desire for a particular mode of human togetherness or, in short, a desire for democracy.